‘Truth or Dare’ Media Based on Game Learning for Science Learning in Fifth-Grade Elementary Students - Putu Jessie Ardi Sudira; Anak Agung Gede Agung; Didith Pramunditya Ambara (Mimbar Ilmu, 2025)
This study was motivated by the low interest and participation of students in Social Science learning (IPAS) on the topic “My Proud Region”, which was caused by the use of monotonous and less interactive teaching methods. The purpose of this study was to develop and examine the effectiveness of a game-based Truth or Dare media for fifth-grade students. This research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fifth-grade students at an elementary school, totaling 25 students. Data collection methods and instruments included questionnaires and tests. Data analysis was conducted using quantitative, qualitative, and inferential descriptive techniques. The results showed that the developed media had a high level of validity, was practical for use by teachers and students, and effectively improved student engagement and material comprehension. The t-test results indicated that H₀ was rejected and H₁ accepted, leading to the conclusion that the game-based Truth or Dare media is effective for teaching the Social Science topic “My Proud Region” to fifth-grade students. The implication of this study is that simple game-based media can serve as an innovative, contextual, and enjoyable alternative for learning, particularly in Social Science subjects at the elementary school level.